AUTOMATED IP CAMERA: ATTENDANCE BASED APPLICATION USING FACIAL RECOGNITION - HASHIM, MOHD ASYRAF (Universiti Teknologi PETRONAS, 2016)
Facial recognition has become new focus in the area of machine learning application. It is not only encourage new technique to be developed to maximise the recognition rate, it is also give impact on extending the feature of application to the maximum. In this paper, the author utilized the facial recognition technique to develop a system to take the attendance of the students in the class. The area of utilization is at University Technology of PETRONAS, Perak. The author tend to choose this topic as the final year project because the author saw a flaw in current attendance taking which is done manually. These current techniques have many drawbacks such as it is very times consuming and the student can cheat the attendance sheet without any trace. Hence with the existing of the author’s project will encourage other people to evolve and establish new concept towards betterment. The author used the Viola-Jones algorithm to detect a face and used Local Binary Patterns (LBP) to recognize the student’s faces.